Beneficial lactic acid bacteria based bioprocessing of cashew apple juice for targeting antioxidant nutraceutical inhibitors as relevant antidotes to type 2 diabetes. (July 2019) - Kaprasob, Ratchadaporn; Sarkar, Dipayan; Kerdchoechuen, Orapin; Laohakunjit, Natta; Khanongnuch, Chartchai; Shetty, Kalidas
Graphical abstract: Abstract: Beneficial lactic acid bacteria (LAB) were rationally targeted to bioprocess underutilized byproduct cashew apple juice (CAJ) for enhancing phenolic bioactive-associated antioxidant, anti-hyperglycemic, and anti-hypertensive properties for developing antioxidant nutraceutical antidotes relevant for type 2 diabetes. Lactobacillus plantarum, L. casei and Bifidobacterium longum were used to bioprocess CAJ and then aqueous and 12% ethanol extracts of fermented CAJ were analyzed for total soluble phenolic (TSP) content, phenolic acid profile (HPLC), total antioxidant activity, type 2 diabetes relevant α-glucosidase, and α-amylase enzyme inhibitory activities and hypertension relevant angiotensin-I-converting (ACE) enzyme inhibitory activity using in vitro assay models. Overall, high TSP content, moderate to high antioxidant activity, moderate ACE inhibitory activity and high α-glucosidase and α-amylase enzyme inhibitory activity was observed in bioprocessed CAJ. Therefore, this study suggests that bioprocessing of CAJ from cashew byproducts with L. plantarum and L. casei is an effective strategy for obtaining type 2 diabetes relevant antioxidant nutraceuticals.